PENGARUH KOMUNIKASI ORANG TUA TERHADAP KEDISIPLINAN BELAJAR SISWA SMP SWASTA AL-WASHLIYAH 1 - Marini Silian; Widya Utami Lubis (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of parental communication on student learning discipline at SMP Al-Washliyah 1 Medan. The hypothesis proposed is that it is suspected that there is an influence of parental communication on student learning discipline at SMP Al-Washliyah 1 Medan. The research method used is descriptive quantitative approach with the type of research used is descriptive correlational research. Determination of the sample of this research is population research because the sample is less than 100. The population in this study is 33 people to obtain the necessary data, so in this study the researchers used data collection tools in the form of questionnaires and documentation. Based on the results of research at SMP Al-Washliyah using the calculation of the correlation between the two variables Discipline (X) and Parental Communication (Y). The level of student learning discipline is 80.5% in the high category, the level of Parental Communication status is 70.33% in the high category, the level of the influence of parental communication on student learning discipline is r_count 0.441> r_table 0.274. This shows that there is an influence of parental communication on student learning discipline.